Is there a green premium in the green bond market? Systematic literature review revealing premium determinants. (20th January 2021) - MacAskill, S.; Roca, E.; Liu, B.; Stewart, R.A.; Sahin, O.
Abstract: The green bond market is emerging as an impactful financing mechanism in climate change mitigation efforts. Studies investigating this market have revealed the notion of a 'green premium' or 'greenium' within green bond pricing, including insights into influential characteristics and drivers that govern it. However, methodological heterogeneity among these studies has resulted in general ambiguity regarding a consensus over the existence of the green premium. This research addresses this gap through a systematic literature review with the aim of establishing a consensus on the existence, or nonexistence, of a green premium in the green bond market. The review examines studies published between 2007 and 2019. A ranking of the green bond characteristics most likely to exhibit a green premium is organised, including a framework of driving factors. The findings confirm a consensus on the existence of a green premium within 56% of primary and 70% of secondary market studies, particularly for those green bonds that are government issued, investment grade, and that follow defined green bond governance and reporting procedures. The green premium varies widely for the primary market; however, an average greenium of −1 to −9 basis points on the secondary market is observed. Overall, our findings highlight the crucial role of strengthening environmental preferences amongst bond market participants; including implications for bond pricing theory, by suggesting that future bond pricing should consider noneconomic motives of investors, such as environmental preferences; and, for future growth implications as a catalyst towards the financing of climate change mitigation efforts globally. Highlights: Systematic literature review investigates a consensus on a green premium in the green bond market. Drivers of the green bond premium are investigated. Bond characteristics most likely to exhibit a green premium are organised and ranked. A consensus is established on the green premium within green bond prices.